Efficient Configuration of Storage Rack System as Per Nonlinear Static Pushover Analysis under Triangular and Uniform Pattern of Lateral Loading Pattern - Chandrakant Thombare (Pouyan Press, 2018)
The individual components of cold-formed storage rack system are most vulnerable to local and torsional buckling lateral loads in addition to under gravity. Deterministic allotment of strength and ductility in the structural components and performance evaluation of appropriate techniques is considered in the capacity based design of cold-formed pallet rack system. Nonlinear time history analysis (NTHA) and nonlinear static pushover analysis (NSPA) are most commonly followed techniques for seismic performance evaluation of any structural systems. Although, NTHA is the most correct technique of seismic demand forecasting and performance evaluation, it is computationally heavy and even requires the selection and application of relevant set of ground excitations. A simple method for the nonlinear static analysis of complicated structures subjected to gradually increasing lateral loads (pushover analysis) is presented here. This paper presents investigation of efficient configuration of conventional pallet racking system on the basis of seismic performance by using NSPA. Finite element models of two different configurations of conventional pallet racking system are prepared and analyzed on the general purpose FE platform using ABAQUS 6.12 under monotonic unidirectional lateral loads. Results show that conventional pallet racking system with horizontal and inclined bracing is more efficient as evidenced from a fair judgment of the overall displacement, base shear and yielding demands.